Feed-borne Bacillus cereus exacerbates respiratory distress in chickens infected with Chlamydia psittaci by inducing haemorrhagic pneumonia. Issue 3 (3rd May 2020) - Zuo, Zonghui; Li, Qiang; Guo, Yongxia; Li, Xiaohui; Huang, Shujian; Hegemann, Johannes H.; He, Cheng
ABSTRACT: Chlamydia psittaci is an important zoonotic pathogen and its oral route of infection plays an important role in the transmission and persistence. Bacillus cereus (B. cereus) strain, a common contaminant of animal feed and feedstuffs, can cause severe diarrhoea and malnutrition in poultry. In our previous study, a B. cereus strain (Dawu C), isolated from the haemorrhagic lungs of infected chickens, was shown to harbour two virulence genes ( hblC and cytk ) and was able to induce haemorrhagic lesions in the lungs, as well as gizzard erosion and ulceration (GEU) syndrome in broilers. In the present study, we tested the hypothesis that B. cereus -induced GEU would aggravate C. psittaci infection. Our results showed that SPF chickens exposed to B. cereus developed a severe GEU syndrome. More interestingly, prior infection with B. cereus facilitated C. psittaci infection, and aggravated GEU and respiratory distress, which were accompanied by high chlamydial loads in the lungs and severe lesions in respiratory organs. Moreover, levels of local inflammatory cytokines were elevated and T cell responses were impaired in the infected birds. In conclusion, GEU caused by B. cereus may facilitate chlamydial transmission from the ventriculus to the lungs. RESEARCH HIGHLIGHTS Bacillus cereus contributes to the gizzard erosion and ulceration syndrome in chickens. Exposure to Bacillus cereus exacerbates pneumonia in birds following chlamydial infection. Bacillus cereus facilitates persistent chlamydial infection and exacerbates immune responses.